Consumer Sentiment During the COVID-19 Pandemic - Lena Dräger; Dzung Bui; Giang Nghiem; Bernd Hayo (ZBW - Leibniz Information Centre for Economics, 2021)
This paper uses the COVID-19 pandemic as a case study to investigate the direct and indirect effect of beliefs of others on respondent's own beliefs and on their individual consumer sentiment. In a new online consumer survey with randomized control trials (RCTs) in Thailand and Vietnam, we present randomized subgroups of respondents in both countries with information treatments showing cross-country measures of average beliefs from other surveys. The two countries are interesting cases since Thailand ranks lowest in the cross-country survey on approval rates for the government's reaction to the pandemic, while Vietnam has the highest approval rates. This is our ftrst information treatment, which is on average viewed as good news in Vietnam and as bad news in Thailand. In the second treatment, we show evidence of cross-country average appropriateness ratings of the general public's reaction to the pandemic. This treatment is more symmetric across countries, since both approval rates are relatively similar and lie in the middle of the distribution, rather than in the tails. On average, respondents in our survey view this treatment as neutral. Our results suggest that the information treatments only weakly affect consumer sentiment. We only ftnd signiftcant treatment effects in Vietnam, which suggest that both treatments are viewed as positive news in comparison to the control group. However, consumer sentiment in Vietnam is strongly affected by both treatments when they go against respondents' previously held beliefs.
Keywords: E71; H12; I12; I18; Z18; 330; Consumer sentiment; COVID-19; randomized control trial (RCT); survey experiment; second-order beliefs; government trust; macroeconomic expectations; Thailand; Vietnam